Clinicopathological significance of PD-L1 expression in patients with triple-negative breast cancer - Basheska, Neli; Ognenoska-Jankovska, Biljana (Wiley, 2022)
Background: Programmed death ligand 1 (PD-L1) targeted therapy alone or in combination, is now an alternative strategy in several aggressive tumour types. In this respect, triple-negative breast cancer (TNBC) is a potential candidate with limited treatment options and poor outcomes. However, the prognostic value of PD-L1 expression in TNBC patients remains a controversial subject. Aims: This study aimed to investigate the association between the PD-L1 expression and the clinicopathological features of TNBC patients. Methods: A total of 118 samples from patients with TNBC were examined for PD-L1 expression by immunohistochemistry with an SP142 (Ventana) assay from August 2019 to March 2022. All PD-L1 (+) tumour-associated immune cells (IC) were quantified as a percentage of the tumour area. Tumours were classified as PD-L1(+) (≥1%) or PD-L1 (-) (<1%). After excluding 12 metastatic and 5 biopsy samples of primary TNBC tested, the statistical significance of the correlation between PD-L1 status and clinicopathological characteristics of the 101 TNBC patients undergoing primary surgical treatment was determined by chi-square and Fisher’s exact test. Results & Conclusions: PD-L1(+) were 61 (51.7%) of the 118 TNBC patients, whose median age at diagnosis was 60 (range, 23–80). Positive expression of PD-L1 was detected in 54.7% (58/106) of primary cases compared to 25% (3/12) of metastatic TNBC cases (P = 0.049). Among 101 TNBC patients undergoing primary surgery, 56 (55.4%) were PD-L1 (+). PD-L1(+) status was significantly associated with lymphocytic predominant TNBC having high stromal tumour-infiltrating lymphocytes (TILs) expression (>60%, P = 0.038), with carcinomas having higher proliferative index (Ki-67 >35%, P = 0.00085), as well as with carcinomas with medullary features (P = 0.015). No significant correlation was found between PD-L1 status and other variables such as patients’ age, postoperative stage, tumour status, tumour size, lymph nodal status, histological grade, lymphovascular invasion, blood vessel invasion, perineural involvement, and p53 expression. Therefore, our results indicate that PD-L1 expression may be a promising biomarker for the prognosis of TNBC.
Keywords: breast cancer; triple-negative breast cancer; immunihistochemistry; PD-L1